Proposta de um modelo para a gestão da qualidade na cadeia da produção da cana-de-açúcar no estado de São Paulo - Palota, Paulo Henrique (Universidade Federal de São Carlos, 2017)
The sugarcane generates income for the country through the exportation of sugar, ethanol and more recently through energy cogeneration. The globalization and the fact that the prices of the main sugarcane products are linked to commodities exchange and futures, the sugarcane agricultural industry needs to be competitive in each of the chain agents that comprise it. In this context, the quality of sugarcane is of great importance for the sugarcane chain to be competitive. Total Recoverable Sugar (TRS), which is the main quality requirement of sugarcane as it represents the amount of sugar present in sugarcane, fell by around 10% between the years 2009 and 2015. Other quality requirements for sugarcane as mineral and vegetable impurities increased 18.8% and 42.86% between 2008 and 2013, respectively. These factors justify a model for Quality Management of sugarcane. The main objective of this work is to propose a model for the management of quality in the sugarcane production chain that adds value to it. This model is based on the concepts of integration and Supply Chain Quality Management theory in Chain Supply and Supply Chain Quality Coordination in Agro-Food Production. An empirical investigation of multiple cases is carried out in the main agents of the sugarcane production chain in order to identify the deficiencies and the virtues in light of these theories so that they can provide subsidies for the proposal of the model. The results of this research show that, in most cases, there is no integration between the segments of the chain links of sugarcane both upstream and downstream. The model is evaluated by industry experts. This evaluation demonstrated that the model is capable and sufficient in terms of information to meet the needs of its application, has terms of easy understanding to users and is flexible the characteristics of users. In addition to contain elements necessary for quality coordination, contributing to the improvement and preservation of the quality in the product and to reduce costs and losses in the stages of this production chain.
Keywords: Cadeia de produção; Gestão da qualidade em cadeia de suprimentos; Coordenação da qualidade em cadeias agroalimentares; Cana-de-açúcar; Production chain; Supply chain quality management; Quality coordination in agrifood chains; Sugarcane; ENGENHARIAS::ENGENHARIA DE PRODUCAO